2000
DOI: 10.1103/physrevlett.84.3013
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hebb: Exclusive-OR and Biological Learning

Abstract: A learning algorithm for multilayer neural networks based on biologically plausible mechanisms is studied. Motivated by findings in experimental neurobiology, we consider synaptic averaging in the induction of plasticity changes, which happen on a slower time scale than firing dynamics. This mechanism is shown to enable learning of the exclusive-OR (XOR) problem without the aid of error back-propagation, as well as to increase robustness of learning in the presence of noise.Comment: 4 pages RevTeX, 2 figures P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Synaptic plasticity and neuronal plasticity have different effects on a network level [1,2]. Synaptic plasticity affects the transmission of a signal through a link, a synapse, connecting two nodes, neurons, in the network.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic plasticity and neuronal plasticity have different effects on a network level [1,2]. Synaptic plasticity affects the transmission of a signal through a link, a synapse, connecting two nodes, neurons, in the network.…”
Section: Discussionmentioning
confidence: 99%
“…al [10] (table I): 1) an exploratory version by setting β = 10, and 2) a greedy version by setting Fig. 9.…”
Section: Methodsmentioning
confidence: 99%
“…al. [10] used to solve the XOR problem will now be presented. In this work [10], the authors selected the node to activate stochastically where the probability of firing for each node j is:…”
Section: Minibrainmentioning
confidence: 99%
“…Based on the experimental findings by Frey et al 7 and Otmakova et al 13 , Bak and Chialvo 14,15 as well as Klemm et al 16 suggested biologically inspired learning rules for neural networks that combine unsupervised Hebbian (homosynaptic) with reinforcement learning. We call this kind of combination of Hebbian and reinforcement learning Hebb-like learning to indicate that the learning rule is different from Hebb, but contains nevertheless characteristics which are biological plausible.…”
Section: Overview Of Biological and Artificial Learning In Neural Netmentioning
confidence: 99%